ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI PADA UMKM PETERNAKAN BEBEK PETELUR JMFARM MENGGUNAKAN METODE PROCESS COSTING DI KABUPATEN MUARO JAMBI - Nailil Azizah -; Zahra Ramadhani; Mellya Embun Baining (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Duck laying farms are one of the Micro, Small, and Medium Enterprises (MSMEs) that contribute to fulfilling community protein needs and supporting regional economic development. In managing their business, farmers need accurate production cost information to determine appropriate selling prices. This study aims to identify production cost components and calculate the cost of production at JMFARM Duck Laying Farm using the process costing method. This study employed a quantitative descriptive approach using primary data obtained through direct interviews with the business owner and secondary data from relevant literature. The results showed that the total monthly production cost was Rp16,816,667, consisting of feed costs, vitamins and medicines, electricity and water expenses, and depreciation costs of buildings and equipment. The average egg production reached 13,050 eggs per month, with productivity levels ranging from 84% to 90% of the total duck population. Based on the process costing calculation, the cost of production was Rp1,290 per egg. Feed costs were identified as the largest cost component, accounting for 89.20% of total production costs. Therefore, the implementation of the process costing method provides more accurate production cost information that can be used as a basis for pricing decisions and improving business efficiency.